Indigenous Peoples' Cultural Heritage Rights, Debates, Challenges - Xanthaki, Alexandra; Nuorgam, Piia Kristiina; Heinämäki, Leena; Valkonen, Sanna (Brill, 2017)
Indigenous rights to heritage have only recently become the subject of academic scholarship. This collection aims to fill that gap by offering the fruits of a unique conference on this topic organised by the University of Lapland with the help of the Office of the High Commissioner for Human Rights. The conference made clear that important information on Indigenous cultural heritage has remained unexplored or has not been adequately linked with specific actors (such as WIPO) or specific issues (such as free, prior and informed consent). Indigenous leaders explained the impact that disrespect of their cultural heritage has had on their identity, well-being and development. Experts in social sciences explained the intricacies of indigenous cultural heritage. Human rights scholars talked about the inability of current international law to fully address the injustices towards indigenous communities. Representatives of International organisations discussed new positive developments. This wealth of experiences, materials, ideas and knowledge is contained in this important volume.